The charge state of titanium ions in Pd‐doped Ti:CMAS glass and glass‐ceramics. Issue 6 (3rd April 2017) - Golovchak, Roman; Davis, Mark J.; Vullo, Paula; Astashkin, Andrei; Nichols, Laura; Ingram, Adam; Jain, Himanshu
Abstract: We have investigated the role of charge state of Ti in the electronic properties and structure of electrically conductive CMAS‐TiO2 ‐Pd glass and glass‐ceramics by X‐ray photoelectron spectroscopy, electron paramagnetic resonance, positron annihilation lifetime spectroscopy, and fluorescence spectroscopy. These studies suggest the concentration of Ti 3+ ions was, at most, ~0.1 wt% in glass‐ceramics devitrified in the reducing atmosphere of forming gas; no other glass or glass‐ceramic samples exhibited measurable levels of Ti 3+ . The observed fluorescence at liquid nitrogen temperature in parent glasses and glass‐ceramics obtained in air is explained by UV‐induced charge‐transfer processes involving Ti 4+ ions and oxygen surroundings. The X‐ray photoelectron spectroscopy data are correlated with rutile, anorthite, diopside, and titanite crystalline phases identified in Pd‐free and Pd‐doped Ti:CMAS glass‐ceramics earlier.